The Influence of Successful Factors of Business Performance Using of Accounting Information as Moderating Variables on Food MSME Business Owners in Blora Regency, Indonesia - Agung Satria; Sri Dewi Wahyundaru (Department of Islamic Economic, Faculty of Economic and Business, Nahdlatul Ulama Islamic University (UNISNU) Jepara, Indonesia, 2022)
This study aims to determine the effect of owner's knowledge, business scale, business age on the success of business performance by using accounting information as a moderating variable. The COVID-19 pandemic has changed all aspects of human life, from health to the economy. Micro, Small and Medium Enterprises (MSMEs) in Blora Regency are one of the industries affected by the pandemic. The population in this study is the perpetrators of MSMEs owners of Blora specialties. Through this research obtained 30 respondents with various kinds of business. The sampling technique in this study was purposive sampling. Hypothesis testing in this study used multiple linear regression and Moderated Regression Analysis (MRA). Based on the results of research and data analysis using multiple linear regression and MRA shows that: (1) the knowledge of the owner has a significant negative effect on the success of business performance; (2) business scale has a significant positive effect on the success of business performance; (3) business age has a significant negative effect on the success of business performance; (4) the use of accounting information is moderated negatively on the relationship of owner knowledge to the success of business performance; (5) the use of accounting information is moderated positively on the relationship between business scale and business performance success; (6) the use of accounting information which is moderated negatively on the relationship between business age and business performance success.